ANALISIS SISTEM TANDA PADA OBJEK WISATA PENDAKIAN GUNUNG GEDE PANGRANGO - Shierly Everlin; M Garry Saputra (Narada : Jurnal Desain dan Seni, 2019)
Nowadays, the government is trying to improve the quality of the tourism sector in Indonesia. The government has built a lot of supporting facilities for tourists both local and foreign. However, the case of lost mountain climbers is still common. In this research, there will be a discussion about the sign system that provides people with information in Gunung Gede Pangrango Nationa Park. This study is also discussing a little about the natural conditions on some of these mountains.The study was conducted by direct observation of the climbing site to see and analyze directly the existing sign system. In addition, a number of statistical data will be collected from the management by means of a short interview which will be used as supporting data or secondary data in the study. This research is a qualitative study by conducting a literature study. This literature study was carried out during the sign system analysis process.Placement of signs, legibility and the durability of materials in extreme mountain weather conditions are the aspects to be analyzed based on the science of Visual Communication Design. This research was conducted so that the manager, both local and government, are able to give more attention to the application of the sign system along the climbing track so that it can help reduce the possibility of a climber getting lost.